2019
DOI: 10.3390/su11051254
|View full text |Cite
|
Sign up to set email alerts
|

Young Romanians’ Transition from School to Work in a Path Dependence Context

Abstract: For the past 25 years, Romania crossed a contradictory evolution between the social–educational and economic aspects. From the inflexible educational system of the totalitarian regime, when all graduates from different levels of education immediately received a job (to avoid unemployment—a phenomenon that the communist authorities did not tolerate), there was a transition to an educational system marked by frequent structural and methodological changes and by an increasing gap between the educational offer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…However, these actions also influenced public opinion, as Romanian expatriates were blamed and vilified for spreading COVID-19 ( 18 ). In response to this, messages targeted at both the local population and returning citizens were delivered by government authorities and public personalities, including religious figures ( 19 , 20 ). These actions not only informed the public about the COVID-19 epidemic, but also limited the stigmatization of returning expatriates.…”
Section: Returning Citizens and The Importation Of Covid-19 Cases Intmentioning
confidence: 99%
“…However, these actions also influenced public opinion, as Romanian expatriates were blamed and vilified for spreading COVID-19 ( 18 ). In response to this, messages targeted at both the local population and returning citizens were delivered by government authorities and public personalities, including religious figures ( 19 , 20 ). These actions not only informed the public about the COVID-19 epidemic, but also limited the stigmatization of returning expatriates.…”
Section: Returning Citizens and The Importation Of Covid-19 Cases Intmentioning
confidence: 99%
“…It is important to respect age diversity beside other factors when pursuing the dismissal and the need to provide outplacement. As the level of an employee qualification increases with age, the rate of unemployment has been shown to be related to age and associated qualifications, thus decreasing with age [89]. Experience confirmed that employees participating in outplacement can find a new job faster [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…I. Cuza, Romania) focus on "Young Romanians' Transition from School to Work in a Path Dependence Context". This study analyses this issue in Romania, in a context in which, "from the inflexible educational system of the totalitarian regime, when all graduates from different levels of education immediately received a job (to avoid unemployment-a phenomenon that the communist authorities did not tolerate), there was a transition to an educational system marked by frequent structural and methodological changes and by an increasing gap between the educational offer and the real necessities of the labor market" [13] (p. 1). Furthermore, the authors argue that "in the light of the Sociology of Education, the difficulties met by the new generations that enter the labor market after following a previously established educational model, often intended to be changed according to European sociological principles, but with deeply rooted mentalities and structure, actually difficult to alter" [13] (p. 1).…”
mentioning
confidence: 99%
“…This study analyses this issue in Romania, in a context in which, "from the inflexible educational system of the totalitarian regime, when all graduates from different levels of education immediately received a job (to avoid unemployment-a phenomenon that the communist authorities did not tolerate), there was a transition to an educational system marked by frequent structural and methodological changes and by an increasing gap between the educational offer and the real necessities of the labor market" [13] (p. 1). Furthermore, the authors argue that "in the light of the Sociology of Education, the difficulties met by the new generations that enter the labor market after following a previously established educational model, often intended to be changed according to European sociological principles, but with deeply rooted mentalities and structure, actually difficult to alter" [13] (p. 1). This paper concludes that, "when evaluating the results of this study in the context of the Sociology of Education and sustainable development, it can be noticed that the previously established educational model, along the evolution of contemporary Romania, still plays a major role, with the mentalities and structure of the educational system being difficult to change.…”
mentioning
confidence: 99%
See 1 more Smart Citation